Structural Design for Dora Hospital - Abu Rayan, Mousa; Hroub, Hamdan; Karajat, Wafa' (جامعة بوليتكنك فلسطين - مباني, 2021)
Government and private hospitals are one of the most important institutions that serve our country and serve our people. They provide services and health care to them and provide them with the necessary treatment requirement It is necessary from all diseases, especially because we are suffering today from an increase in the population and the services and treatment that it requires all sides. The project is a hospital in the city of Dura, it is a city with a large population so that it needs a hospital to serve this number of residents, as health centers in the city have become unable to meet the needs of this population and there has been a trend from the government several years ago this construction the hospital. The project consists of 5 floors *Two level floors, each with an area of 726 m 2. *The ground floor area is 3667 m 2. *The first floor has an area of 1893 m 2. *The second floor has an area of 1881 m 2. *The total project area is 8893 m 2. *The land area required for the hospital must not be less than 11,000 square meters.
CD , no of pages 96, مباني 17/2020
Keywords: Structural Designs; Hospital Buldings